Disseminated Rhinosporidiosis Presenting as a Patellar Mass: A Case Report - Kirthi Nath K V; Nivedha G (Annals of Pathology and Laboratory Medicine, 2026)
Background: Rhinosporidiosis is a chronic granulomatous disease caused by *Rhinosporidium seeberi*, an aquatic protistan organism belonging to the class Mesomycetozoea. Although the nasal mucosa is the most commonly involved site, dissemination to bone is exceedingly rare, with patellar involvement being exceptionally uncommon and often mimicking malignancy. Case Presentation: A 55-year-old male presented with slowly progressive swelling over the left patellar region. He had a history of recurrent scalp rhinosporidiosis treated surgically over two decades. Clinical examination revealed multiple polypoidal skin nodules over the trunk and extremities. Radiographs showed a lytic lesion involving the patella, and MRI suggested a primary bone malignancy. However, histopathological examination of tru-cut biopsy followed by patellectomy revealed numerous thick-walled sporangia containing endospores infiltrating the synovium and bony trabeculae, confirming disseminated rhinosporidiosis.Conclusion: Osseous rhinosporidiosis is an extremely rare entity that can closely mimic aggressive bone tumours radiologically. Histopathological examination remains the gold standard for diagnosis. Awareness of such atypical presentations, particularly in endemic regions, is essential to avoid misdiagnosis and ensure appropriate management.